2019
DOI: 10.3390/app9142850
|View full text |Cite
|
Sign up to set email alerts
|

A New Modeling Method of Angle Measurement for Intelligent Ball Joint Based on BP-RBF Algorithm

Abstract: The rotation orientation and the angle of precision of an intelligent ball joint cannot be automatically obtained in passive motion. In this paper, a new method based on a Hall sensor with a permanent magnet (PM) is proposed to identify the spatial rotation orientation and angle. The basic idea is to embed a PM on a ball while the Hall sensors are arrayed into the ball socket. When the ball rotates, the Hall sensor array detects the variation of the magnetic induction intensity in space. By establishing a math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To verify the decoupling method in Section 2, we write the simulation results shown in Figure 3 as a matrix shown in Equation (9). According to the decoupling operation method shown in Equation ( 12), we obtained the simulated results and compared the simulation ones with the theoretical data to verify the decoupling method.…”
Section: Finite Element Simulation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the decoupling method in Section 2, we write the simulation results shown in Figure 3 as a matrix shown in Equation (9). According to the decoupling operation method shown in Equation ( 12), we obtained the simulated results and compared the simulation ones with the theoretical data to verify the decoupling method.…”
Section: Finite Element Simulation and Analysismentioning
confidence: 99%
“…It is unsuitable for precise angle measurement. Therefore, both Shaohui Foong's team and Penghao Hu's team used artificial intelligence algorithms to improve the magnetic effect method [6][7][8][9][10][11]. After the improvement, the measurement accuracy and resolution were significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the measurement model was established using an ANN algorithm. The experimental results showed that the measurement accuracy of the prototype after using the ANN algorithm greatly improved; the range was within ±20°, the single axis measurement accuracy was 4’, and the resolution was 15” [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of shallow ML models are the support vector machine (SVM) invented by Cortes and Vapnik [2] in 1995, and neural networks (NN). Numerous shallow ML models have been deployed in many research fields, including speech and natural language processing, computer vision, and public opinion mining [3][4][5][6][7]. The linear and nonlinear shallow models have gained impressive results in regression and prediction studies, including the prediction of airport passenger throughput with high accuracy [8][9][10].…”
Section: Introductionmentioning
confidence: 99%